THE NATIONAL CHARM OF MIRTEMIR’S POETRY (Scientific journal of the Fergana State University, 2026)
This article provides an extensive analysis of the national characteristics and stylistic originality of Mirtemir’s poetry, focusing on issues of artistic mastery. The author examines the poet’s creative efforts to achieve expressiveness, emotional impact, popularity among the people, and melodiousness in his works.